A bibliometric analysis of global research hotspots and development trends in diabetic wound treatment - Wen, Yin; Nie, Kaiyu (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetic wounds are a serious complication for diabetic patients, characterized by refractoriness, high recurrence rates, and susceptibility to infection. Although current guidelines recommend evidence-based treatment strategies, clinical outcomes remain suboptimal. This paper reviews the current research status and development trends in diabetic wound treatment.MethodsArticles on diabetic wound treatment published between 2014 and 2023 were identified using the Web of Science Core Collection database, resulting in a total of 9,099 articles. Bibliometric methods were employed to analyze authors, institutions, countries, journals, keywords and references using CiteSpace and VOSviewer.ResultsChina has published the most articles in the field, followed by the United States. Shanghai Jiao Tong University is the leading institution in diabetic wound treatment research, and David G. Armstrong from the United States has made significant contributions to this field. “Wound Repair and Regeneration” was identified as the most influential journal. Cluster analysis of keywords revealed four main categories: (1) mechanisms of diabetic wound healing, (2) prognosis, (3) treatment, and (4) management.ConclusionThis paper systematically reviews the research on diabetic wound treatment from 2014 to 2023, outlining and forecasting global research hotspots and trends. Future research is expected to focus on treatment strategies for diabetic wounds, while interdisciplinary collaboration and advancements in intelligent management technologies have the potential to improve patient outcomes.